2014
DOI: 10.1186/s13058-014-0487-6
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic cells contribute directly to the quiescent stem cell population in the adult mouse mammary gland

Abstract: IntroductionStudies have identified multi-potent stem cells in the adult mammary gland. More recent studies have suggested that the embryonic mammary gland may also contain stem/progenitor cells that contribute to initial ductal development. We were interested in determining whether embryonic cells might also directly contribute to long-lived stem cells that support homeostasis and development in the adult mammary gland.MethodsWe used DNA-label retention to detect long label-retaining cells in the mammary glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 40 publications
3
35
0
1
Order By: Relevance
“…Thus, promiscuous labelling and subsequent expansion of even a single lineage-restricted MaSC could resemble clonal expansion of a bipotent MaSC26. In this context it is important to note that the expression of K14 and K18 is differentially regulated in the pre-pubertal mammary gland with some luminal cells unexpectedly expressing K14 (refs 30, 31). Similar difficulties arise with the K8 promoter that is expressed at low levels in a subset of cells, leading to the disparate labelling of luminal cell populations in fate-mapping studies16.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, promiscuous labelling and subsequent expansion of even a single lineage-restricted MaSC could resemble clonal expansion of a bipotent MaSC26. In this context it is important to note that the expression of K14 and K18 is differentially regulated in the pre-pubertal mammary gland with some luminal cells unexpectedly expressing K14 (refs 30, 31). Similar difficulties arise with the K8 promoter that is expressed at low levels in a subset of cells, leading to the disparate labelling of luminal cell populations in fate-mapping studies16.…”
Section: Discussionmentioning
confidence: 99%
“…In lineage tracing experiments marking luminal or basal/ME cells, some studies have shown that lineage restricted progenitor cells maintain the separate epithelial lineages after birth [8284]. Luminal progenitor cells gave rise to mature luminal cells without contribution from a putative stem cell in the basal lineage (Fig.…”
Section: Stem Cell Activity In the Mammary Glandmentioning
confidence: 99%
“…For example, in both humans and mice, rare ERα + cells have been identified that co-label with markers of proliferation, [10–12,126]. Long-term label-retaining studies, which identify slower cycling stem cells or those that undergo asymmetric division, have also identified ERα + cells that retain label [60,84,127,128], suggesting the possibility of an ERα + progenitor cell. Human ERα + long-term label-retaining cells are also enriched for p21 cip , msi-1, and CK19, which have been shown to be putative stem cell markers [128,129].…”
Section: Estrogen and Luminal Progenitor Cellsmentioning
confidence: 99%
“…Studies suggest the origin of mammary stem cells in adult stage is from the proliferating embryonic stem cells of the mammary gland during embryogenesis which has become quiescent in the adult stage [73].…”
Section: Asian J Pharm Clin Resmentioning
confidence: 99%